THE EFFECTS OF BOARD-GAME-BASED LEARNING ON ENGLISH VOCABULARY ACQUISITION AND LEARNER ATTITUDES AMONG THAI UNDERGRADUATE EFL STUDENTS - Jeenpracha, Chayakorn; Meeprom, Benjaporn (วารสารสถาบันวิจัยและพัฒนา มหาวิทยาลัยราชภัฏชัยภูมิ, 2026)
Vocabulary knowledge is central to effective communication in academic and professional settings, yet many Thai undergraduates, particularly non-English majors, have limited opportunities to use new words meaningfully. This study examined English ARENA, a non-digital board-game-based intervention, in relation to English vocabulary acquisition and learner attitudes in a Thai EFL context. A mixed-methods, one-group pretest-posttest quasi-experimental design was used with 50 undergraduates. Data were collected through a vocabulary achievement test, pre- and post-intervention attitude questionnaires, and semi-structured interviews. Vocabulary scores increased from M = 5.44 (SD = 3.63) to M = 9.74 (SD = 4.97). The paired-samples t test showed a statistically significant difference, t(49) = -5.63, p < .001, with a large effect (d = 0.80); a Wilcoxon signed-rank sensitivity analysis led to the same conclusion (Z = -4.47, p < .001). Questionnaire patterns and interview accounts indicated greater enjoyment, confidence, participation, and peer support during gameplay. The qualitative findings also showed that learners valued repeated vocabulary retrieval and contextual use, although unfamiliar rules, time pressure, and difficult words sometimes disrupted play. Taken together, the findings provide preliminary evidence that structured board-game-based learning can support vocabulary acquisition and positive learner experiences in EFL and ESP-oriented classrooms.